ALBERT JAY NOCK TRA STORIOGRAFIA E IDEOLOGIA - Liuti, Arianna (Il Politico, 2024)
Albert Jay Nock denied Germany being solely responsible for WWI in The Myth of a Guilty Nation (1922). Despite his book being the first example of American historical revisionism regarding the causes of the Great War, it has not been widely accepted in historiography. However, Nock’s pioneer self-labeling as a “libertarian”, his military and economic non-interventionism and his radical anti-statism expressed mostly in Our Enemy, the State (1935), significantly influenced the American libertarianism, until the anarcho-capitalism. Frank Chodorov, Ayn Rand, and Murray Newton Rothbard can be considered the Nockian “Remnant”, those “alien spirits” whom preserve a “disinterested regard for the plain intelligible law of things” and defend “the august order of nature”, that is, individual liberty.